The Use of ChatGPT in Higher Education: The Advantages and Disadvantages - Chukwuere, Joshua Ebere (The Indonesian Journal of Computer Science, 2025)
Higher education scholars are fascinated by an artificial intelligence (AI) technology, ChatGPT, developed by OpenAI. Debate exists among the experts on whether or not ChatGPT can support learning. This literature review paper sits within the broader scope of measuring ChatGPT within higher education as a means to understand and produce higher-order learning. The purpose of this paper is to examine essential literature with the goal of providing a balanced contribution around the merits and limitations of the use of ChatGPT in higher education contexts. However, it is also important to examine the potential outcomes, both positive and negative. For this rapid review, the researcher searched Google Scholar, Scopus, and others between January 2023 and July 2023 for prior studies from other publications, and these studies were reviewed. This study found that using ChatGPT in higher education is helpful for many reasons. For example, it provides individualized instruction, spontaneous feedback, access to learning opportunities, and student engagement. There may be some benefits to the learning ecosystem and enjoyment for academics and students. The negative aspects of ChatGPT exist, too. The negatives include the inability to decipher emotion, lack of social interaction, technological limitations, and the risk of becoming overly reliant on ChatGPT in higher education. Higher education should blend ChatGPT with other delivery methods to provide a holistic learning experience to students and lecturers. It is a serious consideration to consider the positives, negatives, and ethical issues when applying ChatGPT in the classroom.